From Waste to Blessings: Waste Management Innovations at Baitul Qur’an Islamic Boarding School: Dari Sampah Jadi Berkah: Inovasi Pengolahan Sampah di Pondok Pesantren Baitul Qur’an - Martalasari, Martalasari; Wahyuni, Sri; Dinata, Marta; Widayat, Prama; Sari, Ermina; Awal, Raudhah (Universitas Lancang Kuning, 2024)
This activity aims to improve the understanding and skills of santri in managing waste, both organic and inorganic, as well as introduce the concept of waste banks and the benefits of magot in waste management. Through a series of educational materials and hands-on practices, participants were invited to care more about the environment and trained to turn waste into valuable resources. The pretest results showed that most participants already had a basic understanding of waste management, but their knowledge of magot and organic waste processing practices were still low. After the mentoring activities, the posttest results showed a significant increase in participants' understanding, especially in distinguishing between types of waste, understanding the benefits of magot, and awareness of the importance of waste management. As many as 93% of participants felt more confident to process organic waste in the boarding school environment, and 96% of participants were committed to inviting friends or family to participate in waste management activities. This shows that this service activity has succeeded in increasing environmental awareness and empowering santri as agents of change in preserving the environment. This activity is expected to be sustainable, with santri as pioneers in waste management in the pesantren environment and surrounding communities, and become an example for similar programs in the future.